Peptide Functionalized Nanoplasmonic Sensor for Explosive Detection - Zhang, Diming; Zhang, Qian; Lu, Yanli; Yao, Yao; Li, Shuang; Jiang, Jing; Liu, Gang Logan; Liu, Qingjun (Nano-Micro Letters, 2015)
In this study, a nanobiosensor for detecting explosives was developed, in which the peptide was synthesized with trinitrotoluene (TNT)-specific sequence and immobilized on nanodevice by Au–S covalent linkage, and the nanocup arrays were fabricated by nanoimprint and deposited with Au nanoparticles to generate localized surface plasmon resonance (LSPR). The device was used to monitor slight change from specific binding of 2,4,6-TNT to the peptide. With high refractive index sensing of 104 nm/RIU, the nanocup device can detect the binding of TNT at concentration as low as 3.12 × 10−7 mg mL−1 by optical transmission spectrum modulated by LSPR. The nanosensor is also able to distinguish TNT from analogs of 2,4-dinitrotoluene and 3-nitrotoluene in the mixture with great selectivity. The peptide-based nanosensor provides novel approaches to design versatile biosensor assays by LSPR for chemical molecules.